Understanding e-book acceptance from a resource-based view perspective: an analysis among students at UiTM Melaka - Muhamad Hanapiyah, Zulkefli; Arham, Ahmad Fadhly; Abdullah, Muhammad Syukri; Jamil, Muhammad Fairuz; Norizan, Nor Sabrena; Koe, Wei-Loon (International Journal of Evaluation and Research in Education (IJERE), 2025)
The COVID-19 pandemic led to a shift in the Malaysian education system from traditional face-to-face teaching to online and open distance learning (ODL). This transition has impacted students, lecturers, and universities. E-books are one technology that supports online learning at the university level. This study aims to investigate the factors influencing e-book acceptance among students. Using quantitative research, a questionnaire was administered to 171 students at Universiti Teknologi MARA (UiTM), Melaka Campus, who are enrolled in strategic management course. The findings reveal a significant impact of course content, instructors, and university support on e-book acceptance. However, there was no significant effect observed for access ability, computer competency and infrastructure. These insights are crucial for universities to plan and implement e-books effectively for their students. As the study is specific to UiTM Melaka Campus, it is recommended that future research encompasses both public and private universities for a more comprehensive understanding.